The Historical Development of Criminal Law: A Comparative Study of Ancient Criminal Law to Contemporary Criminal Law - Mhd. Azhali Siregar (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This research aims to trace and analyze the development of criminal law from ancient times to the contemporary era. Criminal law is an integral part of the legal system that has evolved along with the dynamics of human civilization. In ancient criminal law, as reflected in the Code of Hammurabi, Greek Law, and Roman Law, the approach used emphasized the principles of retribution and social order. The penal system at that time was repressive, rigid, and tended to ignore individual rights, with criminal sanctions being more symbolic and cruel in order to have a deterrent effect. Over time, thinking about criminal law has shifted. The introduction of values of justice, human rights, and modern legal philosophy has influenced the direction of change in criminal law. Contemporary criminal law no longer aims solely at punishment, but also considers aspects of rehabilitation, social reintegration, and victim protection. This development reflects changing societal views on crime, perpetrators, and the function of criminal law itself. In various countries, including Indonesia, criminal law reforms are being implemented to adapt to current challenges, such as globalization, information technology, and transnational crime. This research uses historical methods and a comparative-juridical approach to explore fundamental changes in the structure, function, and purpose of criminal law over time. The results of this study demonstrate that the development of criminal law is not stagnant, but rather continues to transform in response to social, political, and cultural dynamics. By understanding the historical roots and changes that have occurred, it is hoped that a more adaptive, humanistic, and contextual criminal law system can be created, tailored to the needs of modern society.